Influence Maximization with epsilon-Almost Submodular Threshold Functions - Li, Qiang; Chen, Wei; Sun, Xiaoming; Zhang, Jialin (Proceedings of the 31st Annual Conference on Advances in Neural Information Processing Systems (NIPS'2017), 2017)
Influence maximization is the problem of selecting k nodes in a social network to maximize their influence spread. The problem has been extensively studied but most works focus on the submodular influence diffusion models. In this paper, motivated by empirical evidences, we explore influence maximization in the non-submodular regime. In particular, we study the general threshold model in which a fraction of nodes have non-submodular threshold functions, but their threshold functions are closely upper- and lower-bounded by some submodular functions (we call them ε-almost submodular). We first show a strong hardness result: there is no 1/n^[γ/c] approximation for influence maximization (unless P = NP) for all networks with up to n^[γ] ε-almost submodular nodes, where γ is in (0,1) and c is a parameter depending on ε. This indicates that influence maximization is still hard to approximate even though threshold functions are close to submodular. We then provide (1-ε)^[](1-1/e) approximation algorithms when the number of ε-almost submodular nodes is . Finally, we conduct experiments on a number of real-world datasets, and the results demonstrate that our approximation algorithms outperform other benchmark algorithms.